Airport Security Screener Problem-Solving Knowledge and Implications. (December 2020) - Swann, Levi; Popovic, Vesna; Blackler, Alethea; Thompson, Helen
Objective: This research investigates security screeners' knowledge and the effect that differences in knowledge have on the performance of problem-solving activities. We argue that the development of problem-solving knowledge enables security screeners to perform effective problem-solving activity, which assists search and decision-making processes. Background: Airport security screening research has investigated the many variables that affect security screeners' search and decision making during simulated threat-detection tasks. Although search and decision making are essential aspects of security screening, few studies have investigated the problem-solving knowledge and activities that support security screening task performance. Method: Sixteen more-experienced and 24 less-experienced security screeners were observed as they performed x-ray screening in the field at an Australian international airport's departure security checkpoint. Participants wore eye-tracking glasses and delivered concurrent verbal protocol. Results: When interacting with other security screeners, more-experienced screeners demonstrated situational knowledge more than less-experienced screeners, whereas less-experienced screeners experienced more insufficient knowledge. Lag-sequential analysis using combined data from both screener groups showed that situational knowledge facilitated effective problem-solving activity to support search and decision making. Insufficient knowledge led screeners to seek assistance and defer decision making. Conclusion: This study expands current understandings of airport security screening. It demonstrates that security screeners develop knowledge that is specific to problem solving. This knowledge assists effective problem-solving activity to support search and decision making, and to mitigate uncertainty during the x-ray screening task. Application: Findings can inform future security screening processes, screener training, and technology support tools. Furthermore, findings are potentially transferable to other domains.